Maximizing desirable ground beef color with cold storage and display temperatures - Mancini, R.A.; Hunt, Melvin C.; Kropf, Donald H.; Hachmeister, K.A.; Johnson, D.E.; Fox, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study evaluated the combined effects of storage temperature, storage time, display temperature, display time, and fat level on ground beef color. Storage at 32°F minimized discoloration during display compared to storage at 40° and 48°F. Storage up to 12 days at 32°F did not affect ground beef color stability, whereas prolonged storage at 40° and 48°F increased discoloration dramatically. When storage was at 32°F, sales loss was 0.4%, compared to 62% at 48°F. Fat level did not influence discoloration. The use of 32°F during storage and display is essential for maximizing ground beef color life.
Keywords: Beef; Ground beef color; Cold chain management; Discoloration